Pre-organization-mediated macrocylization: efficient synthesis and structural investigations of BINOL-m-phenylenediamine-derived macrocycles - Srinivas, Deekonda; Gonnade, Rajesh G.; Rajamohanan, P. R.; Sanjayan, Gangadhar J. (Tetrahedron Letters, 2008)
This letter describes a serendipitous discovery of an efficient synthetic route to BINOL-m-phenylenediamine-derived macrocycles. These macrocycles are quickly accessible in an one-pot procedure by the direct condensation of (R) and (S) BINOL bis-acids with suitably substituted m-phenylenediamine analogs. Structural investigations by single crystal X-ray crystallography and solution-state NMR studies provided convincing evidence of their intramolecular hydrogen bonding arrangement and rigid structural architecture. The striking feature of these macrocycles is their ready accessibility in optically pure form coupled with their ease of synthesis. (C) 2008 Elsevier Ltd. All rights reserved.